Fractional modeling of COVID-19 dynamics (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
The present work seeks to provide a comparison between the classical epidemiological model using ordinary differential equations and an approach through the fractional calculus, using the COVID-19 pandemic in Brazil as a case study. To do that,we propose a classic SAIRD (susceptible-asymptomaticsymptomatic-recovered-dead) model and its fractional generalization, and we used the 𝐵1 method and the mean squared error to compare and demonstrate which model and strategy is more accurate reproducing the data of COVID-19 in Brazil.
Keywords: Fractional Modeling; Population Dynamics; Computational Strategies; Numerical Methods; COVID-19.